Using macrozoobenthos bioindicators to assess the impact of land use on water quality in Citumang River, Pangandaran District, West Java, Indonesia - NURUL CHAZANAH; SUHARYANTO SUHARYANTO; NUR LAILIAH KAREPESINA; FIKRI ILMI; IMAM ALI AS-SYARIF; IGNATIUS DESPRANTA TARIGAN; STANIA SHEVINA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Chazanah N, Suharyanto, Karepesina NL, Ilmi F, As-Syarif IA, Tarigan ID, Shevina S. 2025. Using macrozoobenthos bioindicators to assess the impact of land use on water quality in Citumang River, Pangandaran District, West Java, Indonesia. Biodiversitas 26: 5964-5976. This study focuses on analyzing macrozoobenthos bioindicators in relation to land use variation along the Citumang River, within the Ciwulan-Cilaki watershed, Pangandaran District, West Java, Indonesia. Previous research has shown that land use along a watershed can influence water quality and macrozoobenthos diversity, as reflected by changes in the diversity index (H'), which tends to be higher in more natural areas (H': 1.06-2.13) and lower in areas under anthropogenic pressure (H': 0.52-1.16). This helps in understanding the relationship between macrozoobenthos diversity and environmental factors driven by land use impacts. Five sampling sites representing natural forest, plantation, agriculture, and residential areas were sampled periodically in May, June, and October 2024. Statistical analyses using PAST version 4.03 included One-Way ANOVA, Hierarchical Cluster Analysis (HCA), Similarity Percentage Analysis (SIMPER), and Canonical Correspondence Analysis (CCA). Significant differences in water quality parameters (p<0.05) were observed among sites with different land use types. HCA and SIMPER revealed distinct macrozoobenthos assemblages corresponding to these variations. Faunus sp., an estuarine species, dominated downstream residential areas with high salinity and organic matter, indicating its role as a potential bioindicator of degraded water quality. In contrast, Clithon sp. and Melanoides sp. were prevalent in upstream natural and agricultural areas, associated with higher dissolved oxygen, water clarity, and nutrient levels, suggesting their suitability as indicators of mildly to moderately polluted conditions. These findings demonstrate that macrozoobenthos communities respond sensitively to land use changes and can effectively indicate variations in riverine environmental quality.